INVESTIGATING THE IMPACT OF SIX-WEEK KETTLEBELL TRAINING ON - Suryaraj, Selvaraj; Rajkumar, Mariyappan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Abstract Background and study aim: Kabaddi requires strength, agility, endurance, and speed for optimal performance. Kettlebell training, known for enhancing functional strength and cardiovascular fitness, has gained popularity, but its impact on kabaddi players' bio motor abilities remains underexplored. To investigate the impact of six-week kettlebell training on selected bio motor abilities and performance variables of kabaddi players. Material and methods: Twenty-four male kabaddi players were randomly assigned to the kettlebell training group (KBTG) (N = 12) (Age: 21.08±0.9, Height: 168.251±3.86, Weight: 65.16±2.32) and control group (CG) (Age: 20.03±0.84, Height: 165.02±4.81, Weight: 57.83±4.36) and their age ranged between 18 and 23. Subjects were randomly selected from the Department of Physical Education, Bharathiar University Coimbatore, Tamil Nadu, India. Twelve subjects underwent kettlebell training (Kettlebell Training Group) and the other 12 underwent regular activity (Control Group). Testing Variables: The study assessed various bio motor abilities and performance variables to evaluate in the impact of kettlebell training. Balance was measured using the standing stroke test, while flexibility was assessed through the sit and reach test. Maximum strength was determined via the 1RM Bench Press. Additionally, toe touch performance was rated subjectively and considered a dependent variable for overall performance assessment. Statistical Analysis: Means and standard deviations (±) described all data, with Shapiro-Wilk tests checking for normality (p< 0.05). A dependent 't' test determined significant mean differences between kettlebell training group and control groups (p < 0.05). Results: The bio motor and performance variables revealed significant improvements in the participants who followed the kettlebell training regimen compared to the control group (p < 0.05). Kettlebell training significantly improved the balance, flexibility, maximum strength, and overall performance in the toe touch of Kabaddi players. Conclusion: Kettlebell training shows significant promise in enhancing bio motor abilities and performance variables of kabaddi players, suggesting its effectiveness over traditional training methods. These findings highlight the need for further research and the potential integration of kettlebell training into kabaddi training programs to optimise player performance.